Visual Media Exposure Interventions Using Digital Cinema, Photography, and Visual Storytelling for Parental Stress Reduction and Coping Enhancement - Hammed Gbenga Adewale (Universal Education Jurnal Teaching and Learning, 2026)
This inquiry explored the impact of specific visual media exposure techniques, namely cinematherapy, photo-therapy, and visual storytelling, on mitigating parental tension and bolstering resilience mechanisms among caregivers of children with neurodevelopmental and behavioral challenges. Utilising a quasi-experimental pre-test–post-test control group framework, forty parents were intentionally recruited and partitioned into three experimental cohorts and one baseline group (n=10 per group). While the control group received no treatment, the experimental participants engaged in structured visual media protocols. Assessment relied on validated metrics: the Parental Stress Scale, the Coping Strategy Indicator, and the Psychosocial Wellbeing Index. Analysis of covariance (ANCOVA) was applied to adjust for initial baseline variances. The analyses revealed a statistically significant main effect of intervention on parental stress, F(3,35) = 9.84, p < .001, partial η² = .46, indicating a substantial reduction in stress among participants in the treatment conditions relative to the control group. Significant gains were also observed in adaptive coping strategies. Specifically, problem solving improved significantly, F(3,35) = 7.62, p = .001, partial η² = .39, and the use of social support increased, F(3,35) = 6.11, p = .002, partial η² = .34. In contrast, no statistically significant effect was found for avoidance coping, F(3, 35) = 1.28, p > .05, suggesting that the interventions did not meaningfully influence avoidance-based responses. Among the tested modalities, cinematherapy proved the most potent for stress reduction and adaptive strategy enhancement, followed by visual storytelling and photo-therapy. These results suggest that visual media serve as a vital supplementary tool for emotional processing and cognitive reappraisal. The study underscores the utility of embedding digital expressive tools into counseling frameworks for families dealing with behavioral deficits. Practitioners like educational psychologists and social workers should consider these as adjuncts to standard care. Future research should prioritise larger cohorts and longitudinal tracking to confirm the scalability of media-based interventions in diverse special needs environments.